CIC/ATXN1-rearranged tumors in the central nervous system are mainly represented by sarcomas: a comprehensive clinicopathological and epigenetic series - Tauziède-Espariat, Arnault; Ebrahimi, Azadeh; Boddaert, Nathalie; Pietsch, Torsten; Grajkowska, Wieslawa; Blau, Tobias; Koch, Arend; Sievers, Philipp; Guillemot, Delphine; Pierron, Gaëlle; Uro-Coste, Emmanuelle; Nicaise, Yvan; et al. (Brain pathology, 2025)
CIC fusions have been described in two different central nervous system (CNS) tumor entities. On one hand, fusions of CIC or ATXN1 genes belonging to the same complex of transcriptional repressors, were reported in the CIC-rearranged, sarcoma (SARC-CIC). The diagnosis of this tumor type, which was recently added to the World Health Organization (WHO) Classification of CNS tumors, is difficult mainly because the data concerning its histopathology (as compared to its soft tissue counterpart), immunoprofile, and clinical as well as radiological characteristics are scarce in the literature. On the other hand, a recent study, based on DNA-methylation profiling, has identified a novel high-grade neuroepithelial tumor characterized by recurrent CIC fusions (HGNET-CIC). The aim of this multicentric study was to characterize a cohort of 15 primary CNS tumors harboring a CIC or ATXN1 fusion in terms of clinical, radiological, histopathological, immunophenotypical, and epigenetic characteristics. According to the integrated diagnoses, 14/15 tumors corresponded to SARC-CIC, and only one to HGNET-CIC. The tumors showed similar clinical (mainly pediatric), radiological (mostly supratentorial, cystic, and contrast enhancing), immunophenotypical (common expression of glioneuronal markers), and genetic (similar spectrum of fusions) profiles but their histopathological appearance was clearly distinct. Moreover, we found a novel fusion transcript (CIC::EWSR1) in a SARC-CIC. Most DNA methylation profiles using the Heidelberg Brain Tumor Classifier (v12.8) annotated the samples to the methylation class “SARC-CIC” (9/14 tumors with available data). By using uniform manifold approximation and projection analysis, four other samples were classified as SARC-CIC and another clustered within the methylation class of HGNET-CIC. Our findings confirm that CNS CIC-fused tumors do not represent a single molecular tumor entity. Further analyses are needed to characterize HGNET-CIC in more detail. These results may help to refine the essential diagnostic criteria for SARC-CIC and their terminology (with a suggested consensual name of sarcoma, CIC/ATXN1-complex rearranged).
Online verfügbar: 23. Oktober 2024
Gesehen am 07.08.2025